Physiological Evaluation of Wheat Genotypes for Tolerance to Water Deficit Stress - Rana, MS; Hasan, MA; Bahadur, MM; Islam, MR (Bangladesh Agronomy Journal, 2018)
Four wheat genotypes (BARI Gom 25, E 28, BAW 1170, BAW1140) were grown under well water and water deficit stress condition to evaluate the sensitivity of physiological traits of wheat resulting reduced grain yield under water deficit stress. Wheat genotypes showed greater stability of flag leaf chlorophyll, greater ability to retain water in leaf, higher level of proline in flag leaf and kernel, higher level of soluble sugar in flag leaf and greater ability to keep the canopy cooler compared to sensitive genotype under water deficit condition. Greater spike dry matter accumulation at peak, longer grain growth duration, better yield components such as spikes m-2 and grains spike-1 under water deficit stress contributed to better tolerance of BARI Gom 25, E 28 and BAW 1170. The order of tolerance based on grain yield was BAW 1170 > BARI Gom 25 > E 28 > BAW 1140 and the order of tolerance based on above ground biological yield was BAW 1170 > E 28 > BARI Gom 25 > BAW 1140. Bangladesh Agron. J. 2017, 20(2): 37-52